2008
DOI: 10.1098/rspb.2007.1700
|View full text |Cite
|
Sign up to set email alerts
|

No effect of blue on winning contests in judo

Abstract: A study by Rowe et al. reported a winning bias for judo athletes wearing a blue outfit relative to those wearing a white one during the 2004 Olympics. It was suggested that blue is associated with a higher likelihood of winning through differential effects of colour on opponent visibility and/or an intimidating effect on the opponent. However, we argue that there is no colour effect on winning in judo. We show that alternative factors, namely allocation biases, asymmetries in prior experience and differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 25 publications
2
34
3
Order By: Relevance
“…This may be linked to the differences in peripheral visibility demonstrated between colours such as red and grey, which assumption was already used in choosing the colour of the outfit of Manchester United (Stephenson, 1999). In contrast to Rowe et al (2005), Dijkstra and Preenen (2008) found no winning bias in judo for blue outfits after controlling for possible confounding factors in the study of Rowe et al (2005) and further analysis of 71 other judo tournaments.…”
Section: Introductioncontrasting
confidence: 51%
“…This may be linked to the differences in peripheral visibility demonstrated between colours such as red and grey, which assumption was already used in choosing the colour of the outfit of Manchester United (Stephenson, 1999). In contrast to Rowe et al (2005), Dijkstra and Preenen (2008) found no winning bias in judo for blue outfits after controlling for possible confounding factors in the study of Rowe et al (2005) and further analysis of 71 other judo tournaments.…”
Section: Introductioncontrasting
confidence: 51%
“…rowe et al [15], when examining the reliability of Hill and barton's results [14], found that judo players in blue won more often than those dressed in white. While it is true that the results of Dijkstra and Preenen [22] indicated that this result [15] could have been caused from that fact that, at least in the initial rounds of the judo match, the uniforms' colors were not allocated randomly as well as being linked to other variables, such as the length of rest between the matches, however, further analysis by Matsumoto et al [19] confirmed rowe et al's data [15]. Matsumoto, besides being psychologist, was also a former athlete and is now a worldclass referee and coach.…”
Section: Introductionmentioning
confidence: 66%
“…However, the existence of a "blue wins over white" effect has not been confirmed beyond all doubt. Analyses by Dijkstra and Preenen (2008) suggest that the results obtained from these studies were an artifact because, first, in the elimination and early rounds of competition, the assignment of uniform color was not absolutely random and, second, the results were influenced by different variables, such as a competitor's length of rest.…”
Section: Introductionmentioning
confidence: 99%
“…Dozens of studies exist demonstrating that the color of a uniform can influence performance in sports (e.g., Attrill et al, 2008;Dijkstra & Preenen, 2008;Hill & Burton, 2005;Kocher & Sutter, 2008;Matsumoto et al, 2007;Mills & French, 1996;Rowe et al, 2005;Tiryaki, 2005), but a great majority of these studies are simply correlations or observations. Even the relatively well researched "red wins" effect was observed in only one experimental study (Hagemann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%